Where is the 'wisdom' in wisdom tooth surgery? A review of national and international third molar surgery guidelines. Issue 5 (May 2021) - Gadiwalla, Y.; Moore, R.; Palmer, N.; Renton, T.
Abstract: The objective of this narrative review was to identify and evaluate published international guidelines on mandibular third molars (M3M) and to assess their clinical scope and the validity of the recommendations. The search strategy used data obtained from a variety of sources including MEDLINE, national regulatory bodies, national dental and surgical colleges and associations, and military medical departments. Adherence to clinical guideline development was investigated using the AGREE II instrument (Appraisal of Guidelines for Research and Evaluation). Sixteen guidelines pertaining to M3M were included in this review. The guidelines produced by the Faculty of Dental Surgery of the Royal College of Surgeons of England (FDS RCS) and Scottish Intercollegiate Guidelines Network (SIGN) were recommended as meeting the criteria for use. Seven other guidelines were recommended but required modifications. The AGREE II instrument provides an excellent framework for guideline assessment. Unfortunately, very few guidelines scored highly across all domains and therefore were not believed to be of high quality. Due to the significant lack of structure and variable standards in guideline development, the conclusions and recommendations of these guidelines are compromised. There is a need for organizations involved in developing M3M guidelines to update guidance periodically in order to ensure that the information available to clinicians and patients is accurate and relevant to clinical practice.